The nonvolatile metabolome of sunflower linear glandular trichomes. (November 2015) - Spring, Otmar; Pfannstiel, Jens; Klaiber, Iris; Conrad, Jürgen; Beifuß, Uwe; Apel, Lysanne; Aschenbrenner, Anna-Katharina; Zipper, Reinhard
Abstract : Graphical abstract: HPLC analysis of the metabolite profile of sunflower trichomes afforded 4 previously undescribed sesquiterpenes of the helibisabonol- and glandulone-type, and proved the presence of various nevadensin derived flavonoids in the same compartment. Highlights: Four new sesquiterpenes were identified. A biogenetic pathway for bisabolene-type sesquiterpenes is proposed. Nonvolatile sesquiterpenes and flavonoids co-occur in sunflower glandular trichomes. Abstract: Uniseriate linear glandular trichomes occur on stems, leaves and flowering parts of Helianthus species and related taxa. Their metabolic activity and biological function are still poorly understood. A phytochemical study documented the accumulation of bisabolene type sesquiterpenes and flavonoids as the major constituents of the non-volatile metabolome of linear glandular trichomes in the common sunflower, Helianthus annuus . Besides known sesquiterpenes of the glandulone, helibisabonol and heliannuol type, four previously undescribed sesquiterpenes named glandulone D, E, F and helibisabonol C were identified by spectroscopic analysis. In addition, four known nevadensin type flavonoids varying in O-methoxy substitutions were found. None of them has previously been reported from Helianthus annuus .